AD, Volume 20, n° 3, 1995 - Full Issue - Journal System, (Africa Development, 1995)
Contents Aux origines de la catastrophe économique de l'Afrique Samir Amin ............................ 5 The Impact of Foreign Aid on Zimbabwe's Agricultural Policy Sam Moyo ............................ 23 The Moral Economy of Working Class Struggle: Strikers, The community and the State in the 1947 Mombassa General Strike Tiyambe Zeleza ................... 51 Etude socioculturelle de l'entreprise sénégalaise Bassirou Tîdjani & Adama Gaye ........................ 89 The Politics of Informal Justice: A Critical Analysis of Informal Process of Justice in Rural Kilba, Mumuye and Jukun of Nigeria Abdul-Mumun Sa'ad ........................... 105 Question nationale et ethnies en Afrique noire: le cas du Sénégal Amady Aly Dieng ................................ 129 Book Reviews Chelewa, Chelewa The Dilemma of Teenage Girls Sophie Β. Oluwole ................................... 157 Evaluating Social Science Research: An Introduction by Thomas R. Black Kibet A Ng'etich. ............................ 163 Publications Received and Acquired ..........................167